SUKSESI DAN PROSPEK PENDIDIKAN AGAMA ISLAM DI TENGAH PERUBAHAN ZAMAN - Supandi Supandi (JURNAL AT-TURAS, 2014)
The patterns of young people behavior that is so far from expectations such as an increase in juvenile delinquency leads many people allege that religious education which is taught in schools or Islamic schools are not able to be a shield for the future nation generation. Therefore reconstruction of Islamic education in the current context and redefinition perspective of Islamic education (PAI) is indispensable. So finally it gives the sense of PAI as a whole and not partial and cause differences and inequality. Some concept maps in applying of PAI in the current context are as follows: 1). integrated cooperation between family and school in the implementation educational tasks. 2. The character education in religious education.